PERCEIVED CAREER-RELATED PRACTICES AND KNOWLEDGE SHARING BEHAVIOUR: A PRELIMINARY STUDY IN OMAN - Faridahwati Mohd. Shamsudin; Said Hamdan Al-Badi; Alexander Bachkirov; Ahmad Said Alshuaibi (Asian Academy of Management Journal, 2016)
We examine the relationship between career-related practices and knowledge sharing behaviour in Oman. The practices considered in this study are perceived security, employability, and promotion opportunities. Although studies on knowledge sharing behaviour at work are plentiful, limited empirical evidence exists of the role of careerrelated practices in this regard. Hence, in fulfilling this gap, a survey was conducted among 129 employees at both managerial and professional levels across various industries in Muscat, Oman. Using multiple regression analysis, the results showed that all practices significantly predicted the dimension of knowledge collecting behaviour, but not knowledge donating behaviour. The implications of the findings on the importance of putting in place practices to support and develop one's career are discussed as a way to promote knowledge collecting in the organisation.